Implementation of Musyarakah Financing Agreement On Sharia Banking (Case Study at Bank BRI Syariah Purwokerto Branch Office) - Muh Rifqi Iqsobayadinur (Authentica, 2020)
Act of Republik Indonesia Number 21 of 2008 concerning Sharia (Islamic) Banking Article 1 Number 13, require all of contract should be written. Thus the implementation of musyarakah financing contract on Islamic banking is needed a notary to make a notariil deed, although there is no a special rule that require a contract must be made with notariil deed. The research is empirical research law to analyzes the data systematically, factual and accurate. The approach used in the research is descriptive qualitative approach. Result of this research indicates that implementation of musyarakah financing contract at PT. BRI Sharia branch of Purwokerto, normatively has been following the elements of the contract, and especially used standard contract from Financial Services Authority (FSA) regulation Number 31/POJK.5/2014 concerning Implementation of Sharia Multi-Finance Business, but substantially there are deviations in which the position of the parties is unbalanced, the nisbah ratio is done unilaterally and is fixed during the funding period, calculation of nisbah is determined at the beginning, and the use of witnesses in contract is not in accordance with sharia principles.Keywords: Contract, Musyarakah Finance, Sharia (Islamic) Banking.